The Influence of Organizational Commitment and Organizational Culture on Employee Performance Through Employee Job Satisfaction as an Intervening Variable (Study on BPJS Employment in Aceh Raya Region) - Kurniadi, Kurniadi; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
This research was conducted to determine the influence of organizational commitment and organizational culture on employee performance through employee job satisfaction as an intervening variable. With the type of quantitative research used, the primary data source used was data collection by distributing questionnaires, a population of 107 employees and a sample of 107 employees and a saturated sampling technique used, this research model is phat analysis, the results of this research are as follows: Culture Organization has a positive and significant effect on Job Satisfaction with an original sample value of 0.687 and ap value of 0.000. Organizational culture has a positive and significant effect on performance with an original sample value of 0.370 and ap value of 0.003. Job satisfaction has a positive and significant effect on performance with an original sample value of 0.338 and ap value of 0.002. Organizational Commitment has a positive and significant effect on Job Satisfaction with an original sample value of 0.237 and a P value of 0.001. Organizational Commitment has a positive and significant effect on performance with an original sample value of 0.198 and a P value of 0.014. Organizational Culture has a positive and significant indirect effect on Performance through Job Satisfaction with an original sample value of 0.232 and a P value of 0.002. Organizational Commitment has a positive and significant indirect effect on Performance through Job Satisfaction with an original sample value of 0.800 and a P value of 0.014.